Revisiting the Concept of Targeting NFAT to Control T Cell Immunity and Autoimmune Diseases - Lee, Jae-Ung; Kim, Li-Kyung; Choi, Je-Min (Frontiers in Immunology, 2018)
The nuclear factor of activated T cells (NFAT) family of transcription factors, which includes NFAT1, NFAT2, and NFAT4, are well-known to play important roles in T cell activation. Most of NFAT proteins are controlled by calcium influx upon T cell receptor and costimulatory signaling results increase of IL-2 and IL-2 receptor. NFAT3 however is not shown to be expressed in T cells and NFAT5 has not much highlighted in T cell functions yet. Recent studies demonstrate that the NFAT family proteins involve in function of lineage-specific transcription factors during differentiation of T helper 1 (Th1), Th2, Th17, regulatory T (Treg), and follicular helper T cells (Tfh). They have been studied to make physical interaction with the other transcription factors like GATA3 or Foxp3 and they also regulate Th cell signature gene expressions by direct binding on promotor region of target genes. From last decades, NFAT functions in T cells have been targeted to develop immune modulatory drugs for controlling T cell immunity in autoimmune diseases like cyclosporine A, FK506, etc. Due to their undesirable side defects, only limited application is available in human diseases. This review focuses on the recent advances in development of NFAT targeting drug as well as our understanding of each NFAT family protein in T cell biology. We also discuss updated detail molecular mechanism of NFAT functions in T cells, which would lead us to suggest an idea for developing specific NFAT inhibitors as a therapeutic drug for autoimmune diseases.